2022
DOI: 10.1371/journal.pmed.1004102
|View full text |Cite|
|
Sign up to set email alerts
|

HIV prevention for the next decade: Appropriate, person-centred, prioritised, effective, combination prevention

Abstract: UNAIDS and a broad range of partners have collaborated to establish a new set of HIV prevention targets to be achieved by 2025 as an intermediate step towards the sustainable development target for 2030. The number of new HIV infections in the world continues to decline, in part due to the extraordinary expansion of effective HIV treatment. However, the decline is geographically heterogeneous, with some regions reporting a rise in incidence. The incidence target that was agreed for 2020 has been missed. A rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…2a shows the age profile of the estimated male and female sources of infection, such that the male plus the female sources sum to 100% for each survey round. Overall, we found that the contribution of men to onward transmission increased progressively from 57.9% [56.1-59.6] in 2003 to 62.8% [60.2-65.2] in 2018, indicating that HIV transmission is now more disproportionely driven by men than has been the case previously.…”
Section: The Proportion Of Transmission From Men Is Increasingmentioning
confidence: 55%
See 1 more Smart Citation
“…2a shows the age profile of the estimated male and female sources of infection, such that the male plus the female sources sum to 100% for each survey round. Overall, we found that the contribution of men to onward transmission increased progressively from 57.9% [56.1-59.6] in 2003 to 62.8% [60.2-65.2] in 2018, indicating that HIV transmission is now more disproportionely driven by men than has been the case previously.…”
Section: The Proportion Of Transmission From Men Is Increasingmentioning
confidence: 55%
“…Effective HIV interventions and services are essential to bring most African countries on track to end AIDS as a public health threat by 2030 and accelerate progress towards the vision of the UNAIDS “three Zeros” target: zero new HIV infections, zero discrimination, and zero AIDS-related deaths 60, 62 . Gender inequalities are among the main reasons why global targets on mass scale-up of HIV testing, biomedical interventions and on incidence reductions have not been achieved 63 .…”
Section: Discussionmentioning
confidence: 99%
“…This resonated with couples and made them feel valued and heard. "Person-centered" approaches to services are recognized as an essential component of high-quality healthcare [28][29][30], particularly in HIV prevention and treatment [31][32][33]. Person-centered services respect individual preferences, PLOS GLOBAL PUBLIC HEALTH are contextually-appropriate, and place wellbeing, agency and empowerment at the center of the health response.…”
Section: Discussionmentioning
confidence: 99%
“…Combination prevention programs include a mix of evidence-based biomedical, behavioral, and structural interventions to meet the current HIV prevention needs of individuals and communities, aiming for the greatest possible impact on reducing the number of people newly infected 2 . They must be appropriate to each individual's circumstances and HIV vulnerability 3 . Globally, gay men and other men who have sex with men are 28 times more likely to be infected with HIV.…”
Section: Introductionmentioning
confidence: 99%